Efficient elimination of U(vi) by polyethyleneimine-decorated fly ash. Issue 10 (10th May 2018) - Pang, Hongwei; Huang, Shuyi; Wu, Yihan; Yang, Dongxu; Wang, Xiangxue; Yu, Shujun; Chen, Zhongshan; Alsaedi, Ahmed; Hayat, Tasawar; Wang, Xiangke
Abstract : The easily-synthesized FA@PEI showed an excellent performance in the elimination of U(vi ) from wastewater, with the adsorption mechanism being explored. Abstract : The toxicity and radioactivity of uranium [ 235, 238 U(vi )] has resulted in serious environmental issues in recent years. Polyethyleneimine-decorated waste fly ash (FA@PEI) from thermal power plants has been fabricated via a novel and cost-efficient method and applied to the U(vi ) elimination from aqueous solutions by batch experiments. The U(vi ) removal was found to be dramatically influenced by pH whilst being ionic strength-independent, which indicated that the interaction was primarily controlled by inner-sphere surface complexation. Kinetic studies showed that the FA@PEI had an ultrafast removal rate (1.5 h to achieve adsorption equilibration) for U(vi ) and a pseudo-second-order model fitted the adsorption process. The maximum removal capacity of U(vi ) by FA@PEI was 70.3 mg g −1 at 298 K and pH 5.0. Based on the thermodynamics data (Δ H ° > 0, Δ S ° > 0 and Δ G ° < 0), the U(vi ) removal process is typically spontaneous and endothermic. According to the XPS analysis, the enhanced U(vi ) adsorption was mainly attributed to the abundant metal–oxide bonds and amine groups (–NH2, –NH–). Furthermore, the FA@PEI material also demonstrated an outstanding regeneration ability. This paper highlights FA@PEI as an environmentally-friendly and economical alternative for U(vi ) elimination from waste water.